Melatih Kemampuan Komunikasi Anak Melalui Program Bahasa Arab di Lembaga Kesejahteraan Sosial Anak (LKSA) Dato’ Rahmat Dasan Baru Bengkel: Training Children's Communication Skills Through the Arabic Language Program at the Dato' Rahmat Dasan Baru Bengkel Child Welfare Institution (LKSA). - Yuliana Susanti; Irwan Hadi; Abdullah (Al-Gafari : Manajemen dan Pendidikan, 2025)
Arabic, as one of the international languages ​​and the main religious language in the Islamic world, requires good mastery to be able to be used actively in various situations, both in social, academic and professional contexts. This study aims to determine the impact of the Arabic language program on the communication skills of children at the Dato' Rahmat Dasan Baru Bengkel Child Welfare Institution (LKSA), as well as the supporting and inhibiting factors in the program's implementation. This study used a qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that the Arabic language program can increase children's confidence in communicating, strengthen religious understanding, and encourage them to be more active. Supporting factors for the program's success include the children's enthusiasm, teacher commitment, and internal support from the institution. Inhibiting factors include limited facilities and infrastructure, limited learning time, and minimal parental involvement. In conclusion, the Arabic language program at LKSA Dato' Rahmat plays an important role in training children's communication skills effectively.